MANAJEMEN KONFLIK DALAM PENDIDIKAN MENURUT PERSPEKTIF ISLAM - Muliati, Indah (TINGKAP, 2016)
ABSTRACTAn educational institution that has low-level conflict, or no conflicts at all, are likely to experience stagnation, not increased, and failed to achieve effectiveness. For that a leader must control conflicts at moderate levels so that these organizations can be dynamic and achieve high effectiveness. If the conflict is at a high level, it is feared that the educational institutions are difficult to control, if not the whole potential of educational institutions used to think of conflict resolution. This will be detrimental to the institution and may even fail to achieve effectiveness. This paper discusses conflict management in education. Conflict management is the ability to control the conflict, which requires specific management skills. Effective conflict management can be realized when it is able to develop and implement a strategy of conflict well. In the teachings of Islam, the conflict is not a goal but a means to bring together various contradictory things to liberate human life and the individual interests of ugliness, so that later gave birth to goodness.Keywords Conflict management, education, educational institution